Analisis Kesiapan Akuntan dalam Menghadapi Transformasi Digital Melalui Cloud Computing: Studi Literatur - Fatimah Azzahra; Nazla Cheryl Khoirunnisa; Senita Laura Putri; Vina Tri Nur Alsya (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
Digital changes have resulted in a fundamental transformation in accounting practices in Indonesia, both in terms of operational mechanisms and professional functions of accountants. The advancement of digital technology drives the transition from manual accounting processes to an integrated model based on data, which requires increased efficiency, pace of work, and accuracy of financial statements. This study intends to evaluate the level of preparation of accountants in handling digital changes, especially related to the implementation of Cloud Computing, by using the literature review method of various relevant domestic studies. The study findings indicate that the preparation of the accountant still shows a considerable variation, which is influenced by digital literacy skills, experience with technology tools, and views on innovation. Accountants who have technology insight and an open attitude towards change are usually more flexible in optimizing digital systems and cloud-based applications. On the other hand, accountants who are familiar with traditional methods face more significant adjustment barriers, especially in terms of changes in work routines and understanding of technological risks. In addition to the technical dimension, the preparation of accountants also involves cognitive and professional aspects, such as understanding of internal control, data protection, and analytical skills in utilizing financial data. This conclusion confirms that the effectiveness of accounting digital transformation depends not only on the accessibility of technology, but also requires the company’s assistance through continuous training programs, flexible internal rules, and a work environment that encourages non-stop learning